UJI EFEKTIVITAS EKSTRAK ETANOL DAUN EKOR NAGA (Rhaphidophora pinnata (L.f) Schott) SEBAGAI ANTIHIPERGLIKEMIA TERHADAP MENCIT PUTIH JANTAN YANG DIINDUKSI SUKROSA - Dian Lestari; Intan Lestari; Fathnur Sani K (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Hyperglycemia is a condition where blood glucose levels increase above normal. Hyperglycemia is a manifestation of diabetes mellitus (DM). Chronic hyperglycemia in diabetes mellitus has an important role in the damage to various organism, including the heart, gynecological eye, nervous and vascular system, which in turn causes complications of diabetes mellitus. Dragon tail leaf extract (Rhaphidophora pinnata (L.f) Schott) contains several compounds that function to reduce glucose in the blood including flavonoids, alkaloids, saponins, steroids and tanins which can inhibit the action of the enzyme α- glucosidase. The purpose of this study was to determine the effect of giving ethanol extract of dragon tail leaves in blood glucose levels and determine the best dose of ethanol extract of dragon tail leaves in reducing blood glucose levels. The samples used were ethanol extract of dragon tail leaves, acarbose as positive control. The study design used was a completely randomized design (CRD) with 5 treatments in which each treatment consisted of 7 mice. The treatment groups are K + acarbose solution at a dose of 50 mg / kgBB, P1 extract dose 125 mg / kgBB, P2 extract dose 250 mg / kgBB, and P3 extract dose 375 mg / kgBB. The testing method used is the Oral Glucose Tolerance Test (OGTT), which is a standard method in the testing antihiperglycemic effect. Observations were carried out for 120 minutes in the time span of 10; 30; 60; 100 and 120 minutes. The research data were analyzed descriptively and One Way ANOVA test. Based on the analysis of the One Way ANOVA test it was found that there were significant differences for each study treatment (p <0.05). Based on Duncan's further tests it was found that the results of the dragon tail leaf extract had antihiperglycemic effect. The best dose of ethanol extract of dragon tail leaves in percent reduction is dose III 375 mg / KgBB with a percent decrease (38,79%). Then followed by dose II 250 mg/KgBB with a percent decrease (17,01%) anf dose I 125 mg/KgBB with percent decrease (5,325%). So it can be concluded that the ethanol extract of dragon tail leaves has effectiveness as an antihiperglycemia.